A New Structure for Cascaded Single-Stage Distributed Amplifier Using Proposed Active Inductor Loads - Kareem, Azad R. (Al-Khwarizmi Engineering Journal, 2017)
A modification to cascaded single-stage distributed amplifier (CSSDA) design by using active inductor is proposed. This modification is shown to render the amplifier suitable for high gain operation in small on-chip area. Microwave office program simulation of the Novel design approach shows that it has performance compatible with the conventional distributed amplifiers but with smaller area. The CSSDA is suitable for optical and satellite communication systems.